Ciliary Neurotrophic Factor Promotes the Activation of Corneal Epithelial Stem/Progenitor Cells and Accelerates Corneal Epithelial Wound Healing. (23rd April 2015) - Zhou, Qingjun; Chen, Peng; Di, Guohu; Zhang, Yangyang; Wang, Yao; Qi, Xia; Duan, Haoyun; Xie, Lixin
Abstract: Ciliary neurotrophic factor (CNTF), a well-known neuroprotective cytokine, has been found to play an important role in neurogenesis and functional regulations of neural stem cells. As one of the most innervated tissue, however, the role of CNTF in cornea epithelium remains unclear. This study was to explore the roles and mechanisms of CNTF in the activation of corneal epithelial stem/progenitor cells and wound healing of both normal and diabetic mouse corneal epithelium. In mice subjecting to mechanical removal of corneal epithelium, the corneal epithelial stem/progenitor cell activation and wound healing were promoted by exogenous CNTF application, while delayed by CNTF neutralizing antibody. In cultured corneal epithelial stem/progenitor cells, CNTF enhanced the colony-forming efficiency, stimulated the mitogenic proliferation, and upregulated the expression levels of corneal epithelial stem/progenitor cell-associated transcription factors. Furthermore, the promotion of CNTF on the corneal epithelial stem/progenitor cell activation and wound healing was mediated by the activation of STAT3. Moreover, in diabetic mice, the content of CNTF in corneal epithelium decreased significantly when compared with that of normal mice, and the supplement of CNTF promoted the diabetic corneal epithelial wound healing, accompanied with the advanced activation of corneal epithelial stem/progenitor cells and the regeneration of corneal nerve fibers. Thus, the capability of expanding corneal epithelial stem/progenitor cells and promoting corneal epithelial wound healing and nerve regeneration indicates the potential application of CNTF in ameliorating limbal stem cell deficiency and treating diabetic keratopathy. Stem Cells   2015;33:1566–1576